A Survey for 3D Flame Chemiluminescence Tomography: Theory, Algorithms, and Applications - Jin, Ying; Situ, Guohai (Frontiers in Photonics, 2022)
Combustion diagnostics play an essential role in energy engineering, transportation, and aerospace industries, which has great potential in combustion efficiency improvement and polluting emission control. The three-dimensional (3D) visualization of the combustion field and the measurement of key physical parameters such as temperature, species concentration, and velocity during the combustion process are important topics in the field of combustion diagnostics. Benefiting from the non-contact and non-intrusive advantages of the optical detection method as well as the advantages of the 3D full-field measurement of the measured field by computational tomography, flame chemiluminescence tomography (FCT) has the ability to realize non-intrusive and instantaneous 3D quantitative measurement and 3D full-field visualization of key physical parameters in the combustion process, which has crucial research significance in combustion diagnostics. In this study, we review the progress of FCT technique. First, we provide an extensive review of practical applications of FCT in state-of-the-art combustion diagnostics and research. Then, the basic concepts and mathematical theory of FCT are elaborated. Finally, we introduce the conventional reconstruction algorithm and proceed to more popular artificial intelligence-based algorithms.